2021
DOI: 10.1177/1359104521994880
|View full text |Cite
|
Sign up to set email alerts
|

Who should we ask about mental health symptoms in adolescents with CFS/ME? Parent-child agreement on the revised children’s anxiety and depression scale

Abstract: Background: One in three adolescents with chronic fatigue syndrome/myalgic encephalomyelitis (CFS/ME) have mental health problems. Multi-informant perspectives are key to psychological assessment. Understanding parent-child agreement is crucial to accurate diagnosis, particularly where severe fatigue limits self-report. Methods: Agreement on the revised children’s anxiety and depression scale (RCADs) was assessed between parents and children with CFS/ME ( n = 93) using Bland-Altman plots, cross tabulations and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…There is also a parent‐report version of the RCADS (RCADS‐P) which has demonstrated good psychometric properties in clinical samples (Ebesutani et al., 2010 ) and school samples (Ebesutani et al., 2011 ). It has been reported that there is a high level of agreement between the child‐report version and the parent‐report version (Serafimova et al., 2021 ). In addition, there has been at least one study showing that the parent version (RCADS‐P) may be employed in even younger children (3–17.5 years), indicating acceptable reliability and validity estimates (Ebesutani et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is also a parent‐report version of the RCADS (RCADS‐P) which has demonstrated good psychometric properties in clinical samples (Ebesutani et al., 2010 ) and school samples (Ebesutani et al., 2011 ). It has been reported that there is a high level of agreement between the child‐report version and the parent‐report version (Serafimova et al., 2021 ). In addition, there has been at least one study showing that the parent version (RCADS‐P) may be employed in even younger children (3–17.5 years), indicating acceptable reliability and validity estimates (Ebesutani et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%